2017
DOI: 10.1039/c7ra12004d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of multifunctional Fe3O4@ZnAl2O4:Eu3+@mSiO2–APTES drug-carrier for microwave controlled release of anticancer drugs

Abstract: In this study, we prepared a carrier possessing a simple structure and composition, but with the microwave-targeted-fluorescence multifunctional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a separate study, Yumei Bu and colleagues developed Fe 3 O4@ZnAl 2 O4:Eu 3+ @mSiO 2 -APTES for drug-delivery applications, harnessing the thermal responsiveness of ZnAl 2 O 4 :Eu 3+ . The study reported that 78.2% of the total drug was released in a controlled manner using on/off cycles of MW irradiation [18]. In a study by Chen et al, MW-responsive nanoparticles of mesoporous cobalt ferrite (H-mCo x Fe 3−x O 4 ) were used to encapsulate a chemotherapy drug called VP16.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, Yumei Bu and colleagues developed Fe 3 O4@ZnAl 2 O4:Eu 3+ @mSiO 2 -APTES for drug-delivery applications, harnessing the thermal responsiveness of ZnAl 2 O 4 :Eu 3+ . The study reported that 78.2% of the total drug was released in a controlled manner using on/off cycles of MW irradiation [18]. In a study by Chen et al, MW-responsive nanoparticles of mesoporous cobalt ferrite (H-mCo x Fe 3−x O 4 ) were used to encapsulate a chemotherapy drug called VP16.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of magnetic nanoparticles (MNPs) in therapy and diagnostics strongly depends on the particles' size, shape, surface properties and terminal functional groups [15]. Thus, the production of drugloaded MNPs is of great importance, but it often requires complex and costly technology [16]. Therefore, the search for novel methods which may simplify the preparation of magnetosensitive nanocomposites is still relevant.…”
Section: Introductionmentioning
confidence: 99%